Methodological implications of assessing ict initiatives from the field of communication [Implicaciones metodológicas de la evaluación de iniciativas tic desde el campo de la comunicación] (2019)
Introduction: This article explains the epistemological implications leading to the generation of a qualitative ICT Evaluation Tool. Such tool was validated through a broad research process which included two pilot tests under the modality of consultancy work. Objective: Investigate the meanings and representations made by the subjects involved in an ICT initiative through the design and testing of a relevant evaluation tool. Materials and methods: Using ethnography, the meanings and representations made by the subjects involved in an ICT initiative were researched through their relationship with technologies. To do this, instruments constituting the ValoraTic Tool were used: focus groups, semi-structured interviews and digital forums. Results: It is possible to analyze the achievements of an ICT initiative through an appropriate evaluation system allowing to analyze issues such as the level of significance of technological tools for users, the generation of indicators that respond to their own contexts, and the social capital achieved in an environment mediated by this type of technology. This is done by using as conceptual bases the vision of education offered by legitimized organizations such as Unesco, and taking advantage of novel digital possibilities such as digital ethnography. Conclusions: ValoraTic constitutes a methodological possibility whose basic principle is to analyze the generation of knowledge in environments mediated by technology, allowing to understand selfcontexts with their structural limitations, in order to reach greater technological appropriation. © Corporacion Universitaria Lasallista.